1993
DOI: 10.1111/j.1365-3083.1993.tb01688.x
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Populations in Different Stages of Induced Hepatic Metastases in Rats: an Immunohistochemical Analysis

Abstract: Macrophages play a role in the host defence against cancer. Little is known about changes in macrophage populations during early metastatic growth. To evaluate the distribution, number and phenotype of macrophages in the development of hepatic metastases in a rat model (Wag/Rij rats and syngeneic CC531 colon carcinoma cell line), an immunohistochemical study was performed with the monoclonal antibodies ED1 (monocytes, and all macrophages), ED2 (resident tissue macrophages, like Kupffer cells) and ED3 (a subpop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1
2

Year Published

1995
1995
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 26 publications
0
24
1
2
Order By: Relevance
“…this may be due to differences among various macrophage subpopulations (Heuff et al, 1993). It is reported that tumour-associated macrophages (TAMs) may be involved in the development of liver metastasis (Martin et al 1989: Heuff et al 1993. Heuff et al (1993) observed tumourinfiltrating macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…this may be due to differences among various macrophage subpopulations (Heuff et al, 1993). It is reported that tumour-associated macrophages (TAMs) may be involved in the development of liver metastasis (Martin et al 1989: Heuff et al 1993. Heuff et al (1993) observed tumourinfiltrating macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that tumour-associated macrophages (TAMs) may be involved in the development of liver metastasis (Martin et al 1989: Heuff et al 1993. Heuff et al (1993) observed tumourinfiltrating macrophages. a peculiar type of TAM.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, most studies describing the in situ KC-tumor cell interactions focused on events occurring 2-3 weeks after tumor cell inoculation, 20,22,34,35 and only a few studies examined the early stages of hepatic metastases (Ͻ 24 hr). 36,37 Routine microscopic methods are not optimal for studying early hepatic metastasis because they require thin sections, low sampling volumes, complicated preparation methods and immunohistochemical procedures. 38 In contrast, confocal laser scanning microscopy (CLSM) enables the study of large sample volumes and sections 50 -100 m thick, facilitating investigation of rare cellular events such as the occurrence of tumor cells in the liver.…”
Section: Liver Sinusoids Harbor Populations Of 2 Important Types Of Imentioning
confidence: 99%
“…These antibodies include ED1, ED2, ED3, Ki-M2R, and TRPM-3 [13, 14, 15, 16, 17, 18]. According to the results from previous immunohistochemical studies on an antigen-induced arthritis in rats [19, 20], ED1-positive monocytes (or newly recruited macrophages) and ED3-positive exudate-type macrophages infiltrated in the early phase of the arthritis, whereas ED2-positive resident (tissue-associated) macrophages were found in the late phase.…”
Section: Introductionmentioning
confidence: 99%